Organochlorine insecticide residue in fresh tomatoes (lycopersicon esculentum) at the farm gate and market. a case study of the Fanteakwa District of Eastern Region of Ghana. - Prah, George (2013)
A Thesis Submitted to the School of Research and Graduate Studies, Department of Theoretical and Applied Biology Kwame Nkrumah University of Science And Technology, Kumasi, In Partial Fulfilment of the requirements for the Award of Master of Science (MSC. ENVIRONMENTAL SCIENCE) October 2013